1978
DOI: 10.1182/blood.v51.6.1039.bloodjournal5161039
|View full text |Cite
|
Sign up to set email alerts
|

Cytogentics of fibroblastic colonies in Ph1-positive chronic myelogenous leukemia

Abstract: The cytogenetic status of bone marrow stromal elements obtained from six patients with Ph1-positive chronic myelogenous leukemia (CML), two in blast crisis, was studied in vitro utilizing the potential of marrow to form surface-adherent colonies morphologically compatible with mesenchymal elements. We demonstrated the absence of both the marker chromosome and other chromosomal abnormalities in all the fibroblastic colonies studied, indicating that the progenitors of such colonies (plaque-forming units in cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Cytogenetic findings were in support of the concept that in CMPD marrow fibrosis represents a reactive process with a non-neoplastic nature of the collagen-producing fibroblasts (Maniatis et al, 1969;Van Slyck et al, 1970;Greenberg et al, 1978;Castro-Malaspina et al, 1982). Pleomorphic appearance associated with abnormalities of maturation and bizarre and pyknotic forms (naked nuclei) were particularly conspicuous in megakaryocytes of patients with AMM (Buyssens and Bourgeois, 1977;Burkhardt et al, 1984Burkhardt et al, , 1986Georgii et al, 1984a,b;Frisch and Bartl, 1985;Wolf and Neiman, 1987).…”
Section: Histological Studiessupporting
confidence: 56%
“…Cytogenetic findings were in support of the concept that in CMPD marrow fibrosis represents a reactive process with a non-neoplastic nature of the collagen-producing fibroblasts (Maniatis et al, 1969;Van Slyck et al, 1970;Greenberg et al, 1978;Castro-Malaspina et al, 1982). Pleomorphic appearance associated with abnormalities of maturation and bizarre and pyknotic forms (naked nuclei) were particularly conspicuous in megakaryocytes of patients with AMM (Buyssens and Bourgeois, 1977;Burkhardt et al, 1984Burkhardt et al, , 1986Georgii et al, 1984a,b;Frisch and Bartl, 1985;Wolf and Neiman, 1987).…”
Section: Histological Studiessupporting
confidence: 56%
“…To determine the origin of the bone marrow fibroblasts in man, we studied three bone marrow transplant recipients conditioned with high doses of drugs and 300-1000 rads total body irradiation. 300 rads is in the range of LDww for total body irradiation in man and 1000 rads is clearly a supralethal dose (Hall, 1973). Post-transplant cytogenetic studies showed that these patients were all completely reconstituted with haematopoietic cells of donor origin .…”
Section: W Colde Et A1mentioning
confidence: 95%
“…Origin and development of fibres must be analysed when studying MMS particularly in regard t o their relationship with the neoplastic haematopoiesis, their extent throughout the bone marrow space and finally the suggested time of generation. Evolution of reticulin and collagen fibres is considered to represent a rather nonspecific response (26), since fibroblasts/-cytes d o not take part in the process of malignant transformation (27,28), as was shown by chromosomal (27)(28)(29)(30)(31)(32) and enzymatic studies (33,34). Novel findings point towards a major role of immune complexes in the pathogenesis of marrow fibrosis particularly in agnogenic myeloid metaplasia with accompanying fibrosclerosis.…”
Section: Discussionmentioning
confidence: 99%